Virus outbreaks and tourism mobility : strategies to counter global health hazards - Kulshreshtha, Sharad Kumar, 1978- (Tourism security-safety and post conflict destinations., 2021)
Virus Outbreaks and Tourism Mobility: Strategies to Counter Global Health Hazardsuses innovative and cutting-edge research to map out the background and impacts of national, regional and international viral outbreaks focusing on new viewpoints to help build effective strategic responses to global health hazards.